PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE, ARUS KAS DAN SUKU BUNGA TERHADAP FINANCIAL DISTRESS (Studi Pada Perusahaan Sektor Perdagangan Eceran Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021) - Adnan Fikri; Buyung Sarita; Ibnu Hajar; Valentinus Amstrong; Enny Wati Enny Wati (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims: (1) to test empirically the effect of total liquidity on financial distress; (2) empirically test the effect of profitability on financial distress; (3) empirically test the effect of leverage on financial distress; (4) empirically test the effect of cash flow on financial distress; (5) Test empirically the effect of interest rates on financial distress. The population in this study are all retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sample of this study were 19 companies from the retail trade sector. The results of the study show that: (1) liquidity has a positive effect on financial distress in retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021; (2) profitability has a positive effect on financial distress in retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021; (3) leverage has a positive and insignificant effect on financial distress in retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021; (4) cash flows have no effect on financial distress in retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021; (5) interest rates have a positive effect on financial distress in retail trade sector companies listed on the Indonesia Stock Exchange in 2018-2021.